Modelling of sediment precipitation containing struvite from aqueous solutions on the inner walls of steel pipelines - Czajkowska, Justyna; Malarski, Maciej; Siwiec, Tadeusz (Archives of environmental protection, 2019)
The complexity and uncontrolled formation of struvite (MgNH4PO4·6H2O) and its deposition in the technological equipment of wastewater treatment plants (WWTPs) are still the subject of research aimed at understanding the causes and proposing a remedial action. In order to reduce the intensity of the precipitation of struvite in wastewater treatment plants, it is recommended, among others, to limit ﬂow velocity to below 1.5 m·s-1. Literature analysis showed that there are no studies on the precipitation of struvite deposits in pipelines. Most studies focus on the deliberate precipitation of struvite, for example phosphorus recovery, resulting in a molar ratio of 1:1:1 (NH4+:PO43-:Mg2+). In fact, in WWTPs, such concentrations do not occur, but there have been cases of the precipitation of this mineral (and its mixtures) in the sludge parts. In this paper, the study aimed at determining conditions for the precipitation of deposits with a signiﬁcant participation of struvite on the inner walls of steel pipes. The study was conducted at a non-stoichiometric concentration of ingredients at different pH values, as well as under dynamic conditions with ﬂow velocity below 1.5 m·s-1. A mathematical formula (ANOVA) that can be used to determine the mass of deposits in relation to the concentration of ammonium, phosphate, pH and ﬂow velocity was developed. Computational models were developed on to investigate struvite precipitation under different pH levels (8.0–9.5) and ionic concentrations. The studies were carried out on solutions containing ammonium (NH4+), phosphate (PO43-), and magnesium (Mg2+), at a ﬂow velocities of 0.4, 0.9 and 1.4 m·s-1. In order to determine the mathematical formula thanks to which the mass of precipitates can be determined, a special pilot study installation was constructed. The XPS surface analysis of sludge from sewage treatment plants showed a similar composition of compounds with sediments obtained in own research. The presence of struvite was suggested, but the share of atomic percentage of bonds to which struvite was classiﬁed is small and amounts to less than 4%. This means that sediments precipitated in the technological installations are a mixture of various compounds of which pure struvite may constitute only a small part.